DOI: 10.1016/s0194-3960(00)13004-5
|View full text |Cite
|
Sign up to set email alerts
|

The changing economic status of disabled women, 1982–1991 Trends and their determinants

Abstract: This study provides an assessment of the intertemporal economic well-being of a representative sample of women who began receiving Social Security Disability Insurance (SSDI) in 1980-81. We compare their economic circumstances over the 1982-1991 period with those of disabled men who also began receiving SSDI in those years and with those of a matched sample of nondisabled women who had sufficient work experience for benefit eligibility should they have become disabled. In 1982, the new SSDI women beneficiaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Although both disabled men and women are subject to discrimination based on their disability, the relationship between economic marginalization and disability is likely intensified for women (Barile, ; Haveman, Holden, Wolfe, Smith, & Wilson, ), although recent empirical research on this issue is scant. Disabled women are less likely to receive the health and rehabilitative care they need to remain economically or socially independent, and they face reduced access to education, employment, and social inclusion compared with disabled men (Leonard Cheshire Disability, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although both disabled men and women are subject to discrimination based on their disability, the relationship between economic marginalization and disability is likely intensified for women (Barile, ; Haveman, Holden, Wolfe, Smith, & Wilson, ), although recent empirical research on this issue is scant. Disabled women are less likely to receive the health and rehabilitative care they need to remain economically or socially independent, and they face reduced access to education, employment, and social inclusion compared with disabled men (Leonard Cheshire Disability, ).…”
Section: Introductionmentioning
confidence: 99%
“…Haveman et al (2000) find that disabled men fare somewhat better than disabled women when comparing the size of family income Stapleton and Burkhauser (2003). using the US Current Population Survey found that mean household income of working-age men without disabilities increased by 12.6% between 1989, a peak year in the 1980s business cycle, and 2000, a peak year in the 1990s business cycle, compared to a fall of 2.9% over the same period for men with disabilities.…”
mentioning
confidence: 96%
“…Women with disabilities are disproportionately overrepresented among those living in poverty (Haveman, Holden, Wolfe, Smith, & Wilson, 2000). Jans and Stoddard (1999) found that over one third of women with disabilities, and 41% of women with severe disabilities lived in poverty, which were among the highest rates for any group.…”
Section: Women With Disabilities and Povertymentioning
confidence: 99%